La investigacion en fincas sobre frijol (Habilla) en Paraguay - Morales, C. (International Center for Tropical Agriculture, 1987)
After technicians from the Agricultural and Livestock Extension Service from Paraguay were trained at CIAT, on-farm research activities started in this country in 1983 with the establishment of IBYAN trials. The different stages of the methodology used in on- farm research are listed; they include diagnosis, expt., and disemination or technology transfer. (CIAT)